THE AUDIT EXPERIENCE AS A MODERATING THE EFFECT OF E-AUDIT IMPLEMENTATION AND THE AUDIT’S WORKING ENVIRONMENT ON THE QUALITY OF AUDIT FINDINGS IN THE FRAUD AUDITING - Cahyono, Yuli Tri; Putri, Devy Anggraeni Widya; Nurharjanti, Nashirotun Nissa (Universitas Muhammadiyah Surakarta, 2020)
The maximum quality of audit findings in fraud auditing is inseparable from the implementation of e-Audit and its implementation requires a good audit work environment. There is an indication of the decreasing trust of beneficiaries in the reliability of audit results due to the increasing number of bribery cases against auditors. This study aims to examine the audit experience as moderating the application of e-Audit and the audit work environment on the quality of audit findings in fraud auditing. The population in this study was the Audit Board of the Republic of Indonesia (AKN 1) in 2020. The method used for sampling was purposive sampling and it was obtained a sample of 30 respondents. The data were analyzed using multiple linear regression analysis methods and moderate regression analysis with the assistance of the SPSS 25 program. The results of this study indicated that there was a positive significance in the application of e-Audit and the audit work environment on the quality of audit findings in fraud auditing, and audit experience did not moderate this research model. Based on the research results, it is concluded that the application of e-Audit and the audit work environment had an effect on the quality of audit findings in fraud auditing, and audit experience did not moderate the application of e-Audit and the audit work environment on the quality of audit findings in fraud auditing